Enzymatic Digestion of Hyaluronan-Based Brain Extracellular Matrix in vivo Can Induce Seizures in Neonatal Mice - Balashova, Alena; Pershin, Vladimir; Zaborskaya, Olga; Tkachenko, Natalia; Mironov, Andrey; Guryev, Evgeny; Kurbatov, Leonid; Gainullin, Murat; Mukhina, Irina (Frontiers in Neuroscience, 2019)
It is well-known that hyaluronic acid (HA) as a component of brain extracellular matrix (ECM) plays a pivotal role in the nervous system and is involved in synaptic plasticity changes in vascular cognitive impairment and dementia. HA breakdown is a feature of the acute stage of stroke injury and may be detrimental through enhancement of the inflammatory response. Recent studies had shown that knockout mice lacking hyaluronic acid synthetase demonstrates epileptic phenotype in vivo and removal of HA leads to delayed development of epileptiform activity in cultured hippocampal neurons in vitro. Here we studied if digestion of hyaluronic acid in hippocampus in early postnatal period can trigger seizures. Hyaluronidase (Hyal) (5 U/µl) was bilaterally injected into C57BL/6j mice (P17) CA1 field of hippocampus using stereotaxic method to remove hyaluronan-based extracellular matrix. Transcriptome analysis of hippocampal tissue 2 h after enzymatic digestion of hyaluronan-based brain extracellular matrix revealed increased gene expression of proteins involved in inflammation reactions (TLR2, CCL2,3,5), neuroinflammation, axonal guidance and ephrin receptor signaling versus the vehicle group. Mice injected with hyaluronidase exhibited delayed audiogenic seizures, improvement in working memory at the time point 72 hour after injection while there were no changes in locomotor activity, anxious level and exploratory behavior due to the open field test. The obtained results point to a link between the activation of neuroinflammation by enzymatic digestion of hyaluronan-based brain extracellular matrix during the neonatal period and their subsequent reactivity to seizures, which may play an important role in the functional features of the developing brain, including its seizure propensity.